A nutritional study of Irish athletes. Issue 2 (June 1981) - Barry, A.; Cantwell, T.; Doherty, F.; Folan, Jean C.; Ingoldsby, M.; Kevany, J. P.; O'Broin, J. D.; O'Connor, H.; O'Shea, B.; Ryan, B. A.; Vaughan, J.
Abstract : The aims of this study were (1) to carry out a nutritional assessment of selected Irish athletes and (2) to provide individual results and specific advice to each athlete on how to achieve an optimum diet. Dietary intakes were measured by a three-day weighed dietary record technique designed to evaluate each athlete's usual eating habits. The results were evaluated against a set of dietary standards in order to determine adequacy. Nutritional status was also assessed in a limited form by selected anthropometric and biochemical measurements. A total of 148 subjects took part in the assessment which began in May, 1979 and continued until April, 1980. The sports involved included: canoeing, cycling, rowing, swimming, hockey, squash and track and field events. The results indicated a range of sub-optimal dietary patterns relating in particular to abnormal intakes of folate, iron, pyridoxine and calcium. The significance and applications of these findings are discussed.